The degree to which social studies teachers in the South Al Sharqiyah Governorate in the Sultanate of Oman possess the skills of employing artificial intelligence in education - Almasrouri, Fahad Salem Saif (Journal of Curriculum and Teaching Methodology, 2024)
To achieve the objectives of the study, the researcher used the descriptive approach, where the researcher prepared a questionnaire consisting of (34) statements distributed over (3) axes: skills related to the field of planning, skills related to the field of implementation, skills related to the field of evaluation, and after ensuring the validity and reliability of the tool, it was applied to The study sample consisted of (91) male and female teachers in the South Al Sharqiyah Governorate. The study results indicated that the level of social studies teachers' proficiency in employing artificial intelligence in education was 2.56 out of 5, which is considered low. The results also showed that there were no statistically significant differences at the significance level (α = 0.05) between males and females, and between the levels of Years of experience in all axes, The results of the study indicated that the most important training programs proposed to enhance the skills of employing artificial intelligence in education among social studies teachers from their point of view are augmented reality, virtual reality technologies, and the Internet of Things. The researcher recommended the necessity of implementing appropriate workshops and training programs for social studies teachers, with the aim of equipping them with skills for employing artificial intelligence. The study also presented a set of proposals for future studies.
Keywords: skills; artificial intelligence; social studies teachers; education